Open Distance Learning for Development: Lessons from Strengthening Research Capacity on Gender, Crisis Prevention, and Recovery - Babu, Suresh Chandra; Ferguson, Jenna; Parsai, Nilam; Almoguera, Rose (International Review of Research in Open and Distributed Learning, 2013)
This paper documents the experience and lessons from implementing an e-learning program aimed at creating research capacity for gender, crisis prevention, and recovery. It presents a case study of bringing together a multidisciplinary group of women professionals through both online and face-to-face interactions to learn the skills needed to be a successful researcher. It reviews the issues related to distance learning programs with particular reference to the e-learning courses and highlights the constraints and challenges in implementing them. Lessons from the experience for future development of similar courses indicate that participant profiling prior to the course, user friendliness of technology, meeting various learning styles, encouraging and rewarding online exchanges, commitment of course moderators, a variety of learning materials, and mixed approaches to learning are some of the factors that can enhance the success of e-learning programs. The paper concludes that enhancing skills of developing country researchers through e-learning programs can increase learning accessibility to those living and working in remote and conflict ridden areas, and bring together a network of professionals to interact and exchange experiences on common problems and solutions.